2020
DOI: 10.1002/advs.202001467
|View full text |Cite
|
Sign up to set email alerts
|

Multiresolution Imaging Using Bioluminescence Resonance Energy Transfer Identifies Distinct Biodistribution Profiles of Extracellular Vesicles and Exomeres with Redirected Tropism

Abstract: Extracellular particles (EPs) including extracellular vesicles (EVs) and exomeres play significant roles in diseases and therapeutic applications. However, their spatiotemporal dynamics in vivo have remained largely unresolved in detail due to the lack of a suitable method. Therefore, a bioluminescence resonance energy transfer (BRET)-based reporter, PalmGRET, is created to enable pan-EP labeling ranging from exomeres (<50 nm) to small (<200 nm) and medium and large (>200 nm) EVs. PalmGRET emits robust, sustai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 61 publications
6
74
0
1
Order By: Relevance
“…Some work has tried to give solutions to this issue, and they build their own quantification platforms based on antibodies, immunoassay, and imaging flow cytometry, which are able to selectively detect tumor‐derived EVs 151–153 . And in their work, compared to healthy donors, cancerous samples are able to release more EVs, and gene knockdown of organ‐tropic membrane proteins could decrease organ‐tropic EVs to specific organ 154 . This might indicate that increasing of EVs secretion promotes cancer progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some work has tried to give solutions to this issue, and they build their own quantification platforms based on antibodies, immunoassay, and imaging flow cytometry, which are able to selectively detect tumor‐derived EVs 151–153 . And in their work, compared to healthy donors, cancerous samples are able to release more EVs, and gene knockdown of organ‐tropic membrane proteins could decrease organ‐tropic EVs to specific organ 154 . This might indicate that increasing of EVs secretion promotes cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…[151][152][153] And in their work, compared to healthy donors, cancerous samples are able to release more EVs, and gene knockdown of organ-tropic membrane proteins could decrease organ-tropic EVs to specific organ. 154 This might indicate that increasing of EVs secretion promotes cancer progression. Besides the quantification of sEVs, how sEVs contents are regulated also spawn our attention.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatives to dye labeling methods include genetic modification of cells to express fluorescent or bioluminescent proteins fused with a transmembrane domain of a membrane protein, EV-associated protein, or a membrane-anchoring signal sequence [ 36 ]. Small ATP-independent luciferases such as Gaussia luciferase (Gluc) and NanoLuc have been used for tracking EVs in culture and living subjects [ 82 , 83 , 84 , 85 ]. Since EVs generally lack ATP and extracellular levels of ATP are negligible, the development of these bioluminescent reporters was critical to enabling bioluminescent imaging approaches, which have led to rapid and high-throughput EV screens [ 86 ].…”
Section: Advances In Visualizing Evs In 3d Models and Assessing Their Rolementioning
confidence: 99%
“…One such method is the to use bioluminescence resonance energy transfer (BRET), which allows for both fluorescence and bioluminescence imaging. An example is the PalmGRET reporter utilizing GFP and Nanoluc bioluminescence reporter genes fused to a palmitoylation signal peptide, allowing the reporter to be trafficked to the cell membrane and expressed in EVs [ 84 ]. Mouse hepatocellular carcinoma cells (HCA1) stably expressing PalmGRET EVs were injected into mice and had greater distribution to liver and lungs.…”
Section: Modeling How Tumors Reach Out To Adjacent and Distant Non-malignant Tissues Via Evsmentioning
confidence: 99%
“…These newly discovered exomeres are the predominant extracellular particles released by most cancer cells studied. These three nanoparticles subpopulations (Exo-L, Exo-S, and exomeres) were isolated from the extracellular vesicle (EV) fraction of several cancer and normal cells using asymmetric-flow field-flow fractionation (AF4), showing diverse organ distribution patterns and cargo content, which suggest specific biological functions [ 100 , 130 ]. Zhang et al [ 100 ] investigated the organ biodistribution of B16-F10 melanoma-derived nanoparticles subsets in naïve mice, and found that Exo-L showed tropism for lymph nodes, whereas Exo-L, Exo-S, and exomeres were uptaken by hematopoietic organs (liver, spleen, and bone marrow), whereas lungs and kidneys showed less uptake and Exo-L, Exo-S, and exomeres were absent in the brain.…”
Section: Extracellular Micrornasmentioning
confidence: 99%